2010
DOI: 10.1073/pnas.1012457108
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of reconstructed ancestral H5N1 influenza viruses for cross-clade protective vaccine development

Abstract: Since the reemergence of highly pathogenic H5N1 influenza viruses in humans in 2003, these viruses have spread throughout avian species in Asia, Europe, and Africa. Their sustained circulation has resulted in the evolution of phylogenetically diverse lineages. Viruses from these lineages show considerable antigenic variation, which has confounded vaccine planning efforts. We reconstructed ancestral protein sequences at several nodes of the hemagglutinin (HA) and neuraminidase (NA) gene phylogenies that represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…Ferret antisera (four ferrets per virus) were raised against the four ancestral strains and against 04-VNM (clade 1), 05-MNG (clade 2.2), 02-CHN (clade 2.1), 06-LAO and 06-HKG (clade 2.3.4), and 06-CHN (clade 4) as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferret antisera (four ferrets per virus) were raised against the four ancestral strains and against 04-VNM (clade 1), 05-MNG (clade 2.2), 02-CHN (clade 2.1), 06-LAO and 06-HKG (clade 2.3.4), and 06-CHN (clade 4) as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore compared the cross-reactivity of clades 0, 1, 2.1, 2.2, 2.3, 4, and four "ancestral" H5N1 strains to determine that a virus(es) may be a useful diagnostic reagents. The ancestral strains were created from hemagglutinin (HA) and neuraminidase (NA) sequences computationally generated to represent ancestral nodes within the H5 and N1 phylogenetic trees (8).…”
mentioning
confidence: 99%
“…In the hemagglutinin inhibition assays (HIAs), a serum dilution of 1:40 is considered protective whereas comparable values were found for an ELISA-based and a colorimetric microneutralization assay; however, these values are not applicable to our assay [13], in particular as it was also shown that ELISA values and HIA values do not correlate, not even within the same subtypes [14]. Moreover, because the majority of heterosubtypic antibodies was found to bind a conserved epitope in the stem of the HA protein and did not interfere with hemagglutination [15,16], they would not be detected by HIAs.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, a case study conducted by the United States CDC, and based upon clinical samples taken during the H7N9 event in China, indicated that despite multiple challenges, properly applied next-generation sequencing technologies to detect and assess the properties of emerging intrahost genetic variants can lead to improved risk assessment. Studies have also been conducted on the potential of use of reconstructed ancestral A(H5N1) influenza viruses to develop cross-clade protective vaccines [10], and on the utility of reverse genetics techniques to improve H5N1 vaccine virus growth rates [11]. Long-term goals in efforts to detect and respond to zoonotic influenza outbreaks include the routine use of surveillance and risk-assignment activities based upon the use of genetic sequencing data, followed by the use of reverse genetics approaches to rapidly generate suitable candidate vaccine viruses.…”
Section: New Technologies and Tools For Improving Influenza Vaccine Vmentioning
confidence: 99%